2014
DOI: 10.1186/2049-2618-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemotherapy on the microbiota and metabolome of human milk, a case report

Abstract: BackgroundHuman milk is an important source of bacteria for the developing infant and has been shown to influence the bacterial composition of the neonatal gut, which in turn can affect disease risk later in life. Human milk is also an important source of nutrients, influencing bacterial composition but also directly affecting the host. While recent studies have emphasized the adverse effects of antibiotic therapy on the infant microbiota, the effects of maternal chemotherapy have not been previously studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 59 publications
2
73
0
1
Order By: Relevance
“…Collectively, nutritional HBM and the bacterial species within (73, 74) not only govern both the development and the health of newborn infants (75,76), but also affect optimal bacterial composition and related metabolites of the neonatal gut (77), thus influencing intestinal immunity and disease risk later in life (12). Yet mechanistic insights highlighting the critical role of HBM feeding are limited and require further investigation for understanding the underlying inputs promoting protective and regulated immune signaling that may be fine-tuned by gut microbiota and their induced metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, nutritional HBM and the bacterial species within (73, 74) not only govern both the development and the health of newborn infants (75,76), but also affect optimal bacterial composition and related metabolites of the neonatal gut (77), thus influencing intestinal immunity and disease risk later in life (12). Yet mechanistic insights highlighting the critical role of HBM feeding are limited and require further investigation for understanding the underlying inputs promoting protective and regulated immune signaling that may be fine-tuned by gut microbiota and their induced metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, it has been postulated that HBM not only increases beneficial bacteria within balanced gut microbiota, but also promotes host immune regulation and reduces the risk of NEC in preterm infants (9)(10)(11)(12). However, further mechanistic insights are required to better understand the immune regulation orchestrated by HBM, the beneficial bacteria within, and critical induced metabolites, all of which may control T cell responses (e.g., Th17 cells) intricately involved in mucosal protection and the pathogenesis of proinflammatory diseases (13).…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesizing that species more accustomed to causing disease and carcinogenic reactions might be present and associated with breast cancer, we conducted 2 studies. We were the first to describe a breast microbiome and demonstrate the differences in the breast microbiome between women with cancer and those who are healthy, suggesting a breast microbiome may indeed have some protective properties (Urbaniak et al 2014(Urbaniak et al , 2016b. While not proving cause and effect, the discoveries could open a new line of investigation into "environmental" factors inducing cancer, and a new method to modify this microbiome to one associated with health.…”
Section: Extending the Translation To Women's Healthmentioning
confidence: 95%
“…Continuing with our interest in women's health and knowing that breast feeding reduces the risk of cancer, I hypothesized that beneficial microbes may play a role in this protection. Studies of human milk showed the presence of lactic acid bacteria (Urbaniak et al 2016a) and the rapid change to dysbiosis caused by chemotherapy (Urbaniak et al 2014). With bacteria having access through the nipple to the mammary gland, it made sense that even in those women who never become pregnant or lactated, bacteria could still be within the mammary gland.…”
Section: Extending the Translation To Women's Healthmentioning
confidence: 99%
“…In the first case report, a woman was receiving doxorubicin, bleomycin, vinblastine, and dacarbazine for treatment of Hodgkin's lymphoma and was told that she could resume breastfeeding 12 days after each round of chemotherapy. 9 She was followed for 4 months. Milk samples taken over 4 months indicated a depletion of Bifidobacterium, Eubacterium, Staphylococcus, and Cloacibacteriumin species, whereas an increase of Acinetobacter, Xanthomonadaceae, and Stenotrophomonas species.…”
mentioning
confidence: 99%